2005
DOI: 10.1111/j.1365-2966.2005.09159.x
|View full text |Cite
|
Sign up to set email alerts
|

The HIPASS catalogue — III. Optical counterparts and isolated dark galaxies

Abstract: We present the largest catalogue to date of optical counterparts for H i radio‐selected galaxies, HOPCAT. Of the 4315 H i radio‐detected sources from the H i Parkes All Sky Survey (HIPASS) catalogue, we find optical counterparts for 3618 (84 per cent) galaxies. Of these, 1798 (42 per cent) have confirmed optical velocities and 848 (20 per cent) are single matches without confirmed velocities. Some galaxy matches are members of galaxy groups. From these multiple galaxy matches, 714 (16 per cent) have confirmed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(94 citation statements)
references
References 29 publications
5
88
1
Order By: Relevance
“…Further evidence for this is that virtually no HIPASS H i object is known without an accompanying galaxy or galaxy-component Doyle et al 2005;Meurer et al 2006;Karachentsev et al 2008). This was also demonstrated using disk evolutionary modeling by Taylor & Webster (2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evidence for this is that virtually no HIPASS H i object is known without an accompanying galaxy or galaxy-component Doyle et al 2005;Meurer et al 2006;Karachentsev et al 2008). This was also demonstrated using disk evolutionary modeling by Taylor & Webster (2005).…”
Section: Discussionmentioning
confidence: 99%
“…KK246 is one of over 4500 H i objects detected in the HIPASS survey (HIPASS J2003-31, Meyer et al 2004) and was identified with the optical counterpart galaxy ESO 461-G036 (Doyle et al 2005). It was subsequently observed using the Very Large Array at 21 cm at higher resolution by Kreckel et al (2011), who found that KK246 is surrounded by a very extended H i region, at least ten times the diameter of the stellar disk.…”
Section: Extended H I Regionmentioning
confidence: 99%
“…Galaxy positions were found by Doyle et al (2005) by centring a 15-arcmin SuperCOSMOS image on the HIPASS locations. Overlaid on the image were galaxies found using SExtractor and galaxies in the NASA Extragalactic Database (NED) and 6dFGS.…”
Section: Hipass Analysismentioning
confidence: 99%
“…The resulting galaxy match catalogue is called HOPCAT (the HIPASS Optical Catalogue). Full HOPCAT details can be found in Doyle et al (2005). The galaxies in HOPCAT are taken to be the location of the galaxies, however, for optical magnitudes, the ESO-LV catalogue was used (Lauberts & Valentijn 1989).…”
Section: Hipass Analysismentioning
confidence: 99%
“…We also calculate the stellar mass of this galaxy in order to place these results in context. The R-and I-band magnitudes of 13.33 and 13.34, respectively, were measured by the HIPASS optical counterparts survey (Doyle et al 2005). We use the Bell et al (2003) r − i mass-to-light ratio relation to estimate a stellar mass of 6.2 × 10 8 M , making it the lowest stellar mass object in our sample.…”
Section: Ngc 1427amentioning
confidence: 99%